Effect of wind turbine size on load reduction with active flow control. Issue 3 (1st May 2022) - Gupta, Abhineet; Rotea, Mario A.; Chetan, Mayank; Sadman Sakib, M.; Todd Griffith, D.
Abstract: Decades of wind turbine research, development and installation have demonstrated reductions in levelized cost of energy (LCOE) resulting from turbines with larger rotor diameters and increased hub heights. Further reductions in LCOE by up-scaling turbine size can be challenged by practical limitations due to a mass increase trend. On-blade, active flow control devices have the potential to disrupt this trend by allowing longer blades with less mass through an active load control system. Typically, these load control systems are developed for specific wind turbines, making it difficult to study load reduction trends with turbine size to gain further insights into the benefits and risks of this control technology. This paper quantifies the variation in load reduction, complexity, and robustness of load control systems with flow control actuators for three turbines of increasing size. It is shown that, under limited control authority, load reduction can increase with turbine size provided more elaborate control algorithms are used to preserve the bandwidth and robustness of the control system.